Special Issue: The 250th Anniversary of the Declaration of Independence. - Begley, Robert (Reason Papers)
This article examines the Declaration of Independence as a form of rhetoric that carries real consequences, emphasizing the integration of ethos (moral credibility), logos (structured reasoning), and pathos (emotional appeal) in its enduring power. The signers pledged their “lives, fortunes, and sacred honor,” binding their personal risk to the document’s principles, which transforms it from mere argument into a committed act. The Declaration’s logical structure presents a case for independence grounded in Enlightenment ideas, while its emotional appeals convey the experience of injustice, making it resonate across diverse contexts. Ultimately, the article highlights the Declaration as a moral standard demanding alignment between belief and action, posing a continuing challenge about responsible speech and individual rights in contemporary society.